Application of Whole Genome Sequencing and Pan-Family Multi-Locus Sequence Analysis to Characterize Relationships Within the Family Brucellaceae - Ashford, Roland T.; Muchowski, Jakub; Koylass, Mark; Scholz, Holger C.; Whatmore, Adrian M. (Frontiers in Microbiology, 2020)
The bacterial family Brucellaceae is currently composed of seven genera, including species of the genus Brucella, a number of which are significant veterinary and zoonotic pathogens. The bacteriological identification of pathogenic Brucella spp. may be hindered by their close phenotypic similarity to other members of the Brucellaceae, particularly of the genus Ochrobactrum. Additionally, a number of novel atypical Brucella taxa have recently been identified, which exhibit greater genetic diversity than observed within the previously described species, and which share genomic features with organisms outside of the genus. Furthermore, previous work has indicated that the genus Ochrobactrum is polyphyletic, raising further questions regarding the relationship between the genus Brucella and wider Brucellaceae. We have applied whole genome sequencing (WGS) and pan-family multi-locus sequence analysis (MLSA) approaches to a comprehensive panel of Brucellaceae type strains, in order to characterise relationships within the family. Phylogenies based on WGS core genome alignments were able to resolve phylogenetic relationships of 31 non-Brucella spp. type strains from within the family, alongside type strains of twelve Brucella species. A phylogeny based on concatenated pan-family MLSA data was largely consistent with WGS based analyses. Notably, recently described atypical Brucella isolates were consistently placed in a single clade with existing species, clearly distinct from all members of the genus Ochrobactrum and wider family. Both WGS and MLSA methods closely grouped Brucella spp. with a sub-set of Ochrobactrum species. However, results also confirmed that the genus Ochrobactrum is polyphyletic, with seven species forming a separate grouping. The pan-family MLSA scheme was subsequently applied to a panel of 50 field strains of the family Brucellaceae, isolated from a wide variety of sources. This analysis confirmed the utility of the pan-Brucellaceae MLSA scheme in placing field isolates in relation to recognised type strains. However, a significant number of these isolates did not cluster with currently identified type strains, suggesting the existence of additional taxonomic diversity within some members of the Brucellaceae. The WGS and pan-family MLSA approaches applied here provide valuable tools for resolving the identity and phylogenetic relationships of isolates from an expanding bacterial family containing a number of important pathogens.